Waltz me around again, Willie, around and around and around,' 1906 (Harper & Brothers, 1906)
Harper's Weekly, A Journal of Civilization' political magazine featuring William Randolph Hearst dancing with a Miss B. Cockran to 'The Limerick Song'. Miss B. Cockran is a cross-gendered/crossdressing caricature of New York Representative William Bourke Cockran who has a dance card illustrating his alliances, party-switches, and campaigned filled political career. Names written include: Mr. McKinley, My. Bryan, Mr. Murphy, Mr. Parker, Mr. Challan, and Mr. Hearst. Written beneath is the limerick's text, "Waltz me around again, Willie, around and around and around."